(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A design problem involving design of beam with an opening has been solved as an explanation for the different methods. The design of beam with web openings is done from various methods like plasticity truss method, plastic hinge method, traditional design approach, IS code and AIJ method. After the designing part comparisons have been drawn between the various methods. These comparisons give a clear idea of the pros and cons of these methods. MATLAB as well as Microsoft Excel have been used as a programming tool. It has been concluded that the Plasticity Truss Method provides a more conservative design approach than the Plastic Hinge Method. However the plasticity truss method requires more longitudinal reinforcement in the chord members as compared to the plastic hinge method. In this study, It has been calculated reinforcements for two beams with small opening and large opening respectively, under its ultimate load, for different longitudinal locations of the opening and different lengths of opening. The variations in area of steel have been recorded and explained for variations in these parameters. Two design methods, Traditional Design Method and Plasticity Truss Method, have been used for the beam with small opening, and compared. Beam with large opening has been designed using Plasticity Truss Method and ACI 318. This work also presents the comparison of reinforcements obtained in above case using IS456 and ACI 318. The results have been compared through graphs and possible reasons of difference in results of two theories have been mentioned. This study shows the reinforcement detailing required near the opening region of a beam, which focuses on crack control along with strengthening beam in flexure and shear.